Utility of mtDNA-COI Barcode Region for Phylogenetic Relationship and Diagnosis of Five Common Pest Cockroaches - Saedeh Sadat Hashemi-Aghdam; Golnaz Rafie; Sanaz Akbari; Mohammad Ali Oshaghi (Journal of Arthropod-Borne Diseases, 2017)
Background: Cockroaches are of vital importance medically and hygienically as they can disperse human pathogenic agents and are especially responsible for food contamination and spreading of food borne pathogens. In this study, part of mtDNA-COI gene of five common pest cockroaches was tested for diagnostic and phylogenetic purposes. Methods: We have described barcode region of mtDNA-COI gene of five cockroach species: Blattella germanica, Blatta orientalis, Periplaneta americana, Shelfordella lateralis, and Supella longipalpa, along with the development of a PCR-RFLP method for rapid detection and differentiation of these health pest species. Results: The PCR generates a single 710 bp-sized amplicon in all cockroach specimens, followed by direct sequencing. AluI predicted from the sequencing data provided different RFLP profiles among five species. There was a significant intra-species variation within the American cockroach populations, but no genetic variation within other species. Accordingly, phylogenetic analysis demonstrates common monophyly for cockroach families in agreement with conventional taxonomy. However S. longipalpa (Ectobiidae) diverged as an early ancestor of other cockroaches and was not associated with other Ectobiidae. Conclusion: The PCR-RFLP protocol might be useful when the conventional taxonomic methods are not able to identify specimens, particularly when only small body parts of specimens are available or they are in a decaying condition. mtDNA-COI gene shows potentially useful for studying phylogenetic relationships of Blattodea order.